2020
DOI: 10.1159/000505649
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of First Recovery Step Response following Unexpected Loss of Balance during Walking: A Dynamic Approach

Abstract: Introduction: Many falls in older adults occur during walking and result in lateral falls. The ability to perform a recovery step after balance perturbation determines whether a fall will occur. Aim: To investigate age-related changes in first recovery step kinematics and kinematic adaptations over a wide range of lateral perturbation magnitudes while walking. Methods: Thirty-five old (78.5 ± 5 years) and 19 young adults (26.0 ± 0.8 years) walked at their preferred walking speed on a treadmill. While walking, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 53 publications
2
11
0
Order By: Relevance
“…1 A'-D'), this supports the view that using the COS strategy was the best to control the moving CoM during the multiple-step trials at relatively high perturbation magnitudes, and that this response may not be under volitional control, thus, requiring an automatic response during the first recovery step. The present study results also indicate differences in balance recovery responses in walking [ 25 , 27 ] versus standing. Both Vlutters et al [ 25 ] and Nachmani et al [ 27 ] found that as the perturbation magnitudes increased during self-selected treadmill walking, there were small yet significant decreases in the timing of the step response.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…1 A'-D'), this supports the view that using the COS strategy was the best to control the moving CoM during the multiple-step trials at relatively high perturbation magnitudes, and that this response may not be under volitional control, thus, requiring an automatic response during the first recovery step. The present study results also indicate differences in balance recovery responses in walking [ 25 , 27 ] versus standing. Both Vlutters et al [ 25 ] and Nachmani et al [ 27 ] found that as the perturbation magnitudes increased during self-selected treadmill walking, there were small yet significant decreases in the timing of the step response.…”
Section: Discussionsupporting
confidence: 62%
“…The presence of single-step and multiple-step responses and the strategies of the first recovery step following a unannouced perturbations were verified offline using Windows Media Player (30 frames per-seconds), which allows video clip pauses, running the clip forwards and backwards, and slow motion. The following classifications were used [ 22 , 26 , 27 ]: Loaded-leg sideway stepping (LLSS)—the participant performs his/her initial step sideway with the loaded leg after the perturbation; Unloaded-leg sideway stepping (ULSS)–, the participant performshis/her initial step sideway with unloaded leg after the perturbation; Cross-over stepping (COS) the participant performed his/her stepping with the unloaded leg, while crossing the one leg over the other leg; Hip Abduction—the participant, abducted his/her hip joint of the unloaded leglateraly; Leg Collisions (Col). The unsuccessful balance recovery was defined as a fall into the safety harness system and grasping the harness system anchor straps or the research assistant to maintain their balance.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A larger sample might have provided greater statistical power to show more robust differences in the muscle activation patterns. Second, it is worth mentioning that perturbations were relatively weak and slow compared, for example, to (Handelzalts et al, 2019; Nachmani et al, 2020). This might have prolonged the recovery process.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, older adults tend to respond with a recovery step at lower perturbation magnitudes [ 6 , 7 ] and tend to fall sideways which accounts for almost all hip fractures [ 1 ]. Compared to young adults, kinematic analyses of older adults’ recovery stepping responses during walking demonstrate slower recovery step initiation time, shorter step length, and larger safety margins of stability [ 8 ].…”
Section: Introductionmentioning
confidence: 99%